Retention patterns of the public sector nursing and midwifery workforce in regional and rural settings of southern Queensland, Australia: a 12-year retrospective analysis - Jessica Elliott; Lee O’Malley; Clara Walker; Ansmarie Van Erp; Priya Martin; Hwee Sin Chong; Bahram Sangelaji; Tony Fallon (BMC Nursing)
Abstract Background The aims of this study were to investigate: (a) Specific time points of exit and time spent working in location of the public sector nursing and midwifery workforce in regional, rural, and remote southern Queensland; and (b) the influence of selected demographic, geographic, and employment variables on the risk of leaving a location. Methods A retrospective cohort design was employed using the employment records of 3234 public sector nurses and midwives between January 2010 and December 2021. Employment records were analysed using survival analysis and Coxs proportional hazards regression, using the Andersen-Gill method to account for the inclusion of multiple records for some employees. Results Study results revealed an overall median survival time of 1.83 years for public sector nursing and midwifery professionals. Registered Nurses were the predominant group employed, yet they also exhibited high turnover rates. Nurses and midwives in permanent full-time positions were more likely to leave location than those in part-time roles. Conclusions Retention of nursing and midwifery professionals in rural Queensland is notably low, with high turnover rates among younger nurses and midwives and those in full-time positions. This study underscores the need for targeted retention strategies, such as flexible work arrangements, improved workplace conditions, and comprehensive professional development programs. Results indicate the need to focus nursing and midwifery workforce retention strategies within 12–18 months post recruitment to retain staff to avoid the current pattern of staff turnover. Clinical trial number Not applicable.